USE OF GLOBAL POSITIONING SYSTEM (GPS) FOR BASIC SURVEY ON STUDENTS - Petrisly Perkasa (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
As been coming ages, modern technology integrates into every life aspect including in field survey. Nowadays, one of the modern technology namely Global Positioning System (GPS). The GPS system was first developed by the US Department of Defense used for both military and civilian purposes. This system is designed to provide threedimensional position, speed, and information about world which is not affected by time and weather. Presently, GPS has been widely used by people all over the world who is need information about position, speed or time. To determine the coordinates of points on earth, the receiver requires at least 4 satellites to capture the signal correctly with the coordinates obtained referring to the global datum such World Geodetic System 1984 (WGS'84). GPS is divided into 3 types: Type of navigation or handheld, generally used in battle field or navigation purposes. Some vehicles have been equipped with GPS for navigation aids by adding a map to guide the rider thus rider know which pathway should be chosen to arrived at the destination. GPS mapping is a GPS tool used to calculate an area or create an important route in transit. Type Mapping has an accuracy level between 1-3 meters and mapping types require a base station serving to receive satellite signals and transmit them to a GPS receiver. Geodetic type is the most meticulous and most sophisticated type than navigation or mapping because it has a level of accuracy below 1 meter. The price of geodetic type is most expensive.